Recepcja twórczości Wiktora Jerofiejewa w Polsce - Szymczak, Grzegorz (Przegląd Rusycystyczny, 2013)
Grzegorz Szymczak Uniwersytet Warszawski, Warszawa, Poland g.szymczak@uw.edu.pl ВОСПРИЯТИЕ ТВОРЧЕСТВА ВИКТОРА ЕРОФЕЕВА В ПОЛЬШЕ Резюме В данной статье автор ставит своей задачей охарактеризовать восприятие творчества Виктора Ерофеева в Польше и назвать главные причины его большой популярности среди польских критиков, журналистов и читателей. Статья обсуждает очередные этапы и специфику восприятия творчества автора Русской красавицы в нашей стране с 1990 года по сегодняшний день. Росту популярности писателя в Польше способствовали провокационный характер его произведений, критический образ России в его трорчестве, близкие отношения писателя с Польшей, а также активность Ерофеева в польских СМИ. RECEPTION OF WORKS BY VICTOR EROFEEV IN POLAND Summary The purpose of this article is to present reception of works by Victor Erofeev in Poland and to define the main reasons of his impressive popularity between Polish critics, journalists and readers. The article draws attention on the successive stages and the peculiarity of reception of Erofeev’ works in Poland since 1990 until now. The rising popularity of this writer in our country can be explained by provocative nature of his prose and essays, critical image of Russia in his works, his close relations with Poland, and Erofeev’s activity in Polish mass media.